The Letter that Lives: Mid. Ps. 29 as a Case Study of Anti-Christological Polemic - Benedikt, Miriam (The journal of theological studies, 2016)
Current methodologies in the study of Midrash allow for the hypothesis that Mid. Ps. 29.1 is polemically structured as an exegetical dispute with a christological interpretation of Ps. 29 (LXX 28). Seemingly without provocation, the Midrash abandons traditional readings of the phrase 'םילא ינב 'הל ובה' (‘Ascribe to the Lord, o ye sons of God’), creating a singular repositioning of Ps. 29:1 in the history of rabbinic interpretation by incorporating the Septuagint’s second and mistaken doublet, ‘sons of rams’. This specific reading coincides with Jerome’s translation of Ps. 28:1a in the Hebraica Veritas ( Adferte Domino filios arietum ), as does the martyrological significance that both the rabbinic homilist(s) and Jerome (amongst others) read into the phrase. I argue that the homilist’s foray into the sphere of disputed dogma is a response to his own historical context, undertaken with a view to defending a vision of Israel’s unmediated covenantal life expressed through martyrdom and eschatology. Here is a midrash that could reflect, if not an actual polemic on this particular phrase, at least Jewish resolve to participate in the long-drawn-out contest between two rivals for the much-coveted title ‘sons of God’, through appropriating and subverting dominant modes of cultural authority.